Unusual magnetic damping effect in a silver-cobalt ferrite hetero nano-system - Sharma, Surender K. (2015)
The static and dynamic magnetic response of the newly synthesized CoFe2O4–Ag hetero nano-system showed significant enhancement in the effective energy barrier and reduction of the magnetic hardness of CoFe2O4 upon interaction with non-magnetic Ag as compared to neat CoFe2O4. The observed magnetic properties of CoFe2O4–Ag have been dissected in detail using the superparamagnetic Stoner–Wohlfarth and Neel–Arrhenius/Vogel–Fulcher models with the aid of micromagnetic simulations.